2016
DOI: 10.1038/hgv.2016.21
|View full text |Cite
|
Sign up to set email alerts
|

A spectrum of CYP1B1 mutations associated with primary congenital glaucoma in families of Pakistani descent

Abstract: Glaucoma is the second leading cause of blindness, affecting ~65 million people worldwide. We identified and ascertained a large cohort of inbred families with multiple individuals manifesting cardinal symptoms of primary congenital glaucoma (PCG) to investigate the etiology of the disease at a molecular level. Ophthalmic examinations, including slit-lamp microscopy and applanation tonometry, were performed to characterize the causal phenotype and confirm that affected individuals fulfilled the diagnostic crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Some previous studies conducted on PCG patients from the Pakistani population have shown variable percentages of mutations such as 47.8%, 30%, and 23.1%. 10,12,13 The possible reason behind the identification of low percentage of mutations in our study could be analysis of 32 isolated cases (Figure 1) that may have disease due to nongenetic factors.…”
Section: Discussionmentioning
confidence: 83%
“…Some previous studies conducted on PCG patients from the Pakistani population have shown variable percentages of mutations such as 47.8%, 30%, and 23.1%. 10,12,13 The possible reason behind the identification of low percentage of mutations in our study could be analysis of 32 isolated cases (Figure 1) that may have disease due to nongenetic factors.…”
Section: Discussionmentioning
confidence: 83%
“…33 Until now, more than 150 mutations in CYP1B1 have been determined linked with PCG that account a signicant fraction of the genetic load of familial and sporadic cases of PCG. 34 Previous studies have shown that there are two chromosomal locations for PCG on 2p21 (GLC3A, MIM 231300) and 1p36 (GLC3B), where GLC3A locus colocalizes to the CYP1B1 gene (MIM 601771 or MYOC) on chromosome 2p21. 35 Basically MYOC encodes a 504-amino-acid glycoprotein that contains an olfactomedin domain (residues 246-501) and is known to be the site where the majority (42/46 [91.3%]) of the mutations documented have been identied.…”
Section: Role Of Cyp1b1 In Glaucomamentioning
confidence: 99%
“…They stated that all of these mutations segregated with the disease phenotype in their respective families. 34 Researchers from Germany investigated 12 rare heterozygous missense mutations in TEK by targeted sequencing. Among them four of these TEK mutations (p.E103D, p.I148T, p.Q214P, and p.G743A) cooccurred with three heterozygous mutations in another major PCG gene CYP1B1 (p.A115P, p.E229K, and p.R368H) in ve families.…”
Section: Role Of Cyp1b1 In Glaucomamentioning
confidence: 99%
“…It is noteworthy that CYP1B1 mutations are population specific and have been detected in patients with diverse ethnic backgrounds. (Sheikh et al, 2014, Rauf et al, 2016 The Pakistani population is genetically heterogeneous with combination of several ethnicities.…”
Section: Introductionmentioning
confidence: 99%